The Effect of Financial Reporting Accountability on the Participation Level of UNEJ Student Support to Non-Governmental Organizations - Galang Nusantara Achmad; Zakwan Hammam; Regita Desta Sekar Sari (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims to tested the effect of Financial Reporting Accountability on Unej Student Support Participation to Non-Governmental Organizations. This study uses a descriptive quantitative approach. The population in this study were active students at the University of Jember. The results showed that the value of the significance of 0.000 < 0.005, it can be concluded that the Financial Reporting Accountability variable (X) has a positive effect on the Participation Rate of UNEJ Student Support to Non-Governmental Organizations (Y). While the KD value is 0.417. From this it was found that the importance of financial reporting accountability is one of the responsibilities of non-governmental organizations information to the public, and this can also contribute to obtaining the support of public sympathizers, including students.